Optimizing the Extraction of Keratin from Cattle Hoof Using Central Composite Design - Kelem Tiessasie Yilma; Tamrat Tesfaye; Haymanot Enawgaw; Million Ayele; Derseh Yilie Limeneh; Magdi Gibril; Fangong Kong (Advances in Materials Science and Engineering)
Cattle hoofs are abundantly available by-product sources of organic material from the slaughterhouse. It can be successfully converted into keratin protein. Keratin extracted using alkali hydrolysis has a better conservancy of keratin structure. The purpose of this study is optimizing the extraction of keratin from cuttle hoof. Designing of the experiment, analysis of the results, and optimization of the process parameters have been conducted by central composite design (CCD). Three factors (temperature (A), time (B), and concentration of NaOH (C)) each at five levels have been used to extract the keratin protein from cattle hoof and two response variables (dissolution % and purity %) have been considered in the study. The results obtained demonstrate that extraction temperature, alkali concentration, and time showed a significant effect on the purity and dissolution of keratin. The regression model shows that all factors have positive and significant relation with dissolution percentage whereas only temperature and concentration of NaOH have significant and negative relation with purity percentage. It is observed that the Biuret and Fourier-transform infrared spectroscopy (FTIR) tests showed better preservation of protein structure in extractive keratin. The FTIR spectra, indicates that amide I and amide II occur at a wave length of 1633 and 1542 cm−1 for raw cattle hoof and at wave length of 1650 and 1542 cm−1 for keratin protein, respectively. Thus, it can be concluded that the cattle hoof by-product could offer an alternative keratin source. Finally, the extraction process had an optimum value of 0.5 M NaOH, 60 minutes reaction time, and 55°C temperature with 85% dissolution and 89.6% purity.